The Effect of Using Gamification-Based Learning Media in Increasing Interest in Learning Physical Education State Senior High School - Paisal Abdullatip; Sufyar Mudjianto; Carsiwan (Universitas Negeri Semarang, 2026)
This study is motivated by the declining interest of students in participating in Physical Education, Sports, and Health (PE) learning, which is influenced by the dominance of digital technology, monotonous teaching methods, and the lack of innovative learning media. In the current digital era, students tend to prefer technology-based activities over physical activities, which has an impact on their engagement in PE learning. Therefore, innovative approaches such as gamification-based learning media are needed to create more engaging and interactive learning experiences. This study aims to determine the effect of the use of gamification-based learning media on the interest in learning Physical Education, Sports, and Health of class X students of State Senior High School 15 Bandung. The study used a quantitative approach with a pretest-posttest control group design. The research sample consisted of 85 students determined using the Slovin formula from a total population of 544 students. Data collection was carried out through a Likert scale questionnaire and analyzed using simple linear regression assisted by SPSS 17. The results showed that the use of gamification-based learning media had a significant effect on interest in learning Physical Education, Sports, and Health with a significance value of 0.000, a regression coefficient of 0.655, and an R Square value of 0.461. Thus, gamification-based learning media has proven effective in increasing interest in learning Physical Education and can be an alternative innovative learning approach in senior high schools.